Travel characteristics of suburban residents during the COVID-19 pandemic (case study of Sonosewu, Bantul Regency) - Santi Dewina Inggar (EDP Sciences, 2021)
The existence of COVID-19 pandemic had an impact on residents’ travel, including in Sonosewu Hamlet, Bantul Regency, Indonesia because the government has implemented recommendation to reduce residents’ mobility in order to accelerate the handling of COVID-19. This research is interesting because there was no research that specifically examines the characteristics of residents’ travel during COVID-19 pandemic in the suburbs of Yogyakarta. The purpose of this study was to identify the travel characteristics of the residents of Sonosewu during the COVID-19 pandemic. The data collection was carried out through questionnaire surveys. The data processing and analysis were carried out by using descriptive statistical methods. Based on the results obtained from 328 respondents, it is known that the travel frequency from November 30 to December 6, 2020, tended to be high with 6 to 7 trips a week. The purpose of travel was mostly to work and shopping, and the main travel destinations are Bantul Regency and Yogyakarta City. The result of this research will be useful for the development of knowledge, especially in the field of urban geography and can be taken into consideration by the government for the development of suburban areas.